Efficacy of a lay community health worker (promotoras de salud) program to improve adherence to emollients in Spanish‐speaking Latin American pediatric patients in the United States with atopic dermatitis: A randomized, controlled, evaluator‐blinded study. Issue 1 (20th October 2022) - Chen, Henry W.; Limmer, Emily E.; Joseph, Adrienne K.; Kinser, Kathryn; Trevino, Amanda; Valencia, Angel; Weinheimer, Rachel A.; Youssef, Sara Hassan; Cervantes, Cecilia; Guzman, Maria Teresa; Morales, Ana; Morales, Sandy; et al.
Abstract: Background: Latin American patients in the United States experience significant health disparities. Community health workers ( promotoras de salud ) reduce disparities by providing culturally appropriate education. While educational interventions have been studied in atopic dermatitis (AD), a chronic dermatologic condition affecting children, none have evaluated the use of promotoras in Spanish‐speaking pediatric patients in the United States. Objective: To create and evaluate a promotora ‐led education program for Spanish‐speaking caregivers of Latin American, pediatric patients with AD through a randomized, controlled, evaluator‐blinded study. Methods: Children with moderate/severe AD ( n = 48) were recruited from the pediatric dermatology clinic at Children's Health℠ in Dallas, TX and randomized to receive clinic education ( n = 26) or clinic education plus promotora home visits ( n = 22). The primary outcome was overall adherence to topical emollients over the 12‐week study, quantified by MEMSCap™ devices; several secondary endpoints were evaluated. Results: Intention‐to‐treat analysis revealed a trend toward increased overall adherence to emollients over the 12‐week study period in promotora (median [interquartile range, IQR]: 43% [26%–61%]) versus non‐ promotora (median [IQR]: 20% [11%–49%]) ( p = .09) groups. SCORAD, AD knowledge, and Spanish‐language Parental Quality of Life Questionnaire for AD (Sp‐PIQoL‐AD) improved in both groups, although there was no statistically significant difference between groups. There was a trend toward increased AD knowledge at Week 4 ( p = .06) in the promotora group. Conclusions: A promotora ‐led educational intervention is a promising approach in increasing caregiver medication adherence in pediatric, Latin American patients with AD in the United States. Further research using creative and culturally appropriate strategies to increase medication adherence is necessary to reduce health disparities in other racial and ethnic minority populations in the United States.